2014
DOI: 10.1007/s00393-014-1468-y
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-Massenspektrometrie am Meniskus

Abstract: The concept of a "meniscus report" is introduced for documentation of meniscus tissue specimens integrating histological, histochemical and proteomic data, thereby specifying the degree of degeneration and the assessment of acute or non-acute lesions. Mass spectrometry contributes to an objective histopathology report. An advisory opinion should always be based on close correlation of clinical and morphological evaluations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…MALDI imaging methods have been applied to proteins, peptides, sugars, lipids, and small molecules . Since numerous paraffin blocks are available in the histopathological archives of institutes of pathology worldwide, application of mass spectrometry peptides in FFPE sections seems to be a reasonable method for the classification of various disease processes including cancer, inflammatory, and metabolic diseases (e.g., amyloidosis), and degenerative processes . The application of MALDI imaging for proteomic analysis in histopathological diagnostics was prevented in the past by the slow acquisition speed of existing platforms as well as by limitations in data processing.…”
Section: Discussionmentioning
confidence: 99%
“…MALDI imaging methods have been applied to proteins, peptides, sugars, lipids, and small molecules . Since numerous paraffin blocks are available in the histopathological archives of institutes of pathology worldwide, application of mass spectrometry peptides in FFPE sections seems to be a reasonable method for the classification of various disease processes including cancer, inflammatory, and metabolic diseases (e.g., amyloidosis), and degenerative processes . The application of MALDI imaging for proteomic analysis in histopathological diagnostics was prevented in the past by the slow acquisition speed of existing platforms as well as by limitations in data processing.…”
Section: Discussionmentioning
confidence: 99%
“…FFPE samples can be analyzed and imaged after direct tryptic digestion 154 or after heat-induced antigen retrieval, dewaxing an digestion 155 . MALDI MSI of FFPE tissue has been reported in great numbers recently 10,[156][157][158][159][160][161][162][163][164][165][166][167][168][169][170][171][172][173] . To mention just one example: ovarian cancer FFPE samples were investigated to describe progression, metastases and other factors of cancer development by topographic parameters and molecular information 169 .…”
Section: On-tissue Enzymatic Digestion For Peptide and Protein Imagingmentioning
confidence: 99%
“…FFPE samples can be analyzed and imaged after direct tryptic digestion or after heat-induced antigen retrieval, dewaxing, and digestion . MALDI MSI of FFPE tissue has been reported in great numbers recently. , To mention just one example: ovarian cancer FFPE samples were investigated to describe progression, metastases, and other factors of cancer development by topographic parameters and molecular information . Samples from 31 patients were analyzed, resulting in 3844 distinct peptide sequences, an average of 982 peptide sequences per sample (Figure ).…”
Section: Applicationsmentioning
confidence: 99%
“…Recently, meniscal lesions have been also characterized by MALDI-MSI [98]. It has been shown that traumatic and degenerative meniscal lesions led to knee osteoarthritis [118].…”
Section: Maldi-msi Analysis Of Meniscusmentioning
confidence: 99%